2022
DOI: 10.1093/plcell/koac245
|View full text |Cite
|
Sign up to set email alerts
|

The deubiquitinating enzymes UBP12 and UBP13 positively regulate recovery after carbon starvation by modulating BES1 stability inArabidopsis thaliana

Abstract: BRI1-EMS-SUPPRESSOR1 (BES1), a core transcription factor in the brassinosteroid (BR) signaling pathway, primarily regulates plant growth and development by influencing BR-regulated gene expression. Several E3 ubiquitin ligases regulate BES1 stability, but little is known about BES1 deubiquitination, which antagonizes E3 ligase–mediated ubiquitination to maintain BES1 homeostasis. Here, we report that two Arabidopsis thaliana deubiquitinating enzymes, UBIQUITIN-SPECIFIC PROTEASE12 (UBP12) and UBP13, interact wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…4, A to C). UBP12 and UBP13 have been found to participate in various plant developmental processes, including plant immunity, phytohormone signaling, nutrient response, and growth, by deubiquitinating various ubiquitinated proteins and preventing their proteasomal degradation (43)(44)(45)(46)(47)(48)(49)(85)(86)(87)(88). Our experiments show that UBP12 and UBP13 specifically eliminate polyubiquitin chains from DA2 (Fig.…”
Section: Ubp12 and Ubp13 Regulate Growth By Limiting The Activity Of ...mentioning
confidence: 56%
See 1 more Smart Citation
“…4, A to C). UBP12 and UBP13 have been found to participate in various plant developmental processes, including plant immunity, phytohormone signaling, nutrient response, and growth, by deubiquitinating various ubiquitinated proteins and preventing their proteasomal degradation (43)(44)(45)(46)(47)(48)(49)(85)(86)(87)(88). Our experiments show that UBP12 and UBP13 specifically eliminate polyubiquitin chains from DA2 (Fig.…”
Section: Ubp12 and Ubp13 Regulate Growth By Limiting The Activity Of ...mentioning
confidence: 56%
“…In addition, BRI1 can negatively regulate the activity of DA1 through phosphorylation (70). On top of this, UBP12 and UBP13 have been shown to stabilize BES1 (45,46) and BRI1 (44), and the double transgenic lines BRI1 OE _bb and BRI1 OE _da1-1 synergistically enhance leaf size (98). Therefore, it will be interesting to explore the contributions to organ size in higher-order mutants of both pathways.…”
Section: Protein Fusions Can Trigger the Proteolytic Activity Of Da1mentioning
confidence: 99%
“…Recent studies have reported that BES1 protein abundance is modulated by the deubiquitinating enzymes UBP12 and UBP13 during the recovery process after plants suffer from carbon starvation (Xiong et al., 2022). BES1 interacts with HSFA1 and is activated, resulting in the accumulation of the de‐phosphorylation state protein in response to heat stress (Albertos et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While UBP12/13 do not interact with the E3 ligase NITROGEN LIMITATION ADAPTATION (NLA) of ORE1, they interact with another ligase, ATL31 under high C/low N stress, which is modified with both K48‐ and K63‐linked polyubiquitin chains (Luo et al ., 2022b). During carbon starvation, UBP12/13 fine‐tune the recovery process by managing BES1 stability via cleaving both K48‐ and K63‐linked ubiquitin chains of BES1, a key TF in BR signaling (Park et al ., 2022; Xiong et al ., 2022). As starvation ensues, both BES1 and UBP12/13 levels decline.…”
Section: Ubp12/13 Function In Biotic and Abiotic Stressesmentioning
confidence: 99%
“…Upon recovery, UBP12/13 levels rise, enhancing BES1 and thus BR-mediated growth. Notably, among 27 UBPs in Arabidopsis, only UBP12/13 interact with and deubiquitinate BES1 (Xiong et al, 2022), highlighting the substrate specificity of UBP12/13. UBP12/13 also function in DNA damage responses and gene silencing.…”
Section: Reviewmentioning
confidence: 99%